In vitro evaluation of combination effects of doxorubicin with methylxanthine fractions isolated from Bancha and Pu-erh teas against breast cancer cells - Georgiev, Kaloyan D.; Slavov, Iliya J.; Iliev, Ivan A. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: In the present study we investigated the combination effects of anthracycline antibiotic, doxorubicin, with methylxanthine fractions isolated from Bancha and Pu-erh tea leaves, against MCF-7 and MDA-MB-231 breast cancer cell lines. Methods: Neutral red uptake assay was used for assessment of cytotoxicity effects and fractional effect analysis and combination index for evaluation of the combination effects. Results: Doxorubicin was used in varying concentrations by a double dilution method, whereas the methylxanthine fractions were in fixed concentrations – 100, 200, 400 or 600 μg/ml. Results have shown that methylxanthine fraction isolated from Bancha has synergic effects with doxorubicin, while methylxanthines from Pu-erh displayed antagonistic effects. Conclusions: Тhe obtained results lead us to suspect, that even minor differences in the composition of natural products can lead to significant differences in the biological activity of the product.